2022
DOI: 10.1108/et-01-2021-0029
|View full text |Cite
|
Sign up to set email alerts
|

Is there a gender difference in STEM students' perceived employability?

Abstract: PurposeThe study sought to determine whether there are gender differences in self-perceived employability of students enrolled in Australian higher education science, technology, engineering and mathematics (STEM) programs.Design/methodology/approachUsing an online measure comprised of Likert style and open text items, STEM students (n = 3,134) reported their perceived employability in relation to nine dimensions of employability identified from the literature as having relevance to careers in STEM. Analysis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The existing literature regarding gender-based differences in skills among university students has produced inconsistent findings. Some studies have reported the presence of such differences (Bennett et al ., 2022; Dominic and Fulgence, 2020), whereas others have found no evidence of them (Ain et al ., 2019; Ghimire et al ., 2022). The findings of the present study align with the former perspective, as significant differences in gender were observed for music students' self-appraisal on professional skills and soft skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existing literature regarding gender-based differences in skills among university students has produced inconsistent findings. Some studies have reported the presence of such differences (Bennett et al ., 2022; Dominic and Fulgence, 2020), whereas others have found no evidence of them (Ain et al ., 2019; Ghimire et al ., 2022). The findings of the present study align with the former perspective, as significant differences in gender were observed for music students' self-appraisal on professional skills and soft skills.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic characteristics play a significant role in shaping individuals' perception of employability, with gender being a critical factor (Morley, 2001). In the Science, Technology, Engineering and Mathematics (STEM) students' perceived employability, gender differences were observed across study mode, age and engagement with work through regression-based modeling (Bennett et al, 2022). In a survey to investigate gender differences in enhancing students' employability skills, higher learning institutions are advised to take into account gender differences when designing extra-curricular activities (ECAs) aimed at enhancing students' employability skills.…”
Section: Influencing Factors On Students' Employabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…, 2019) and even personality traits (Neneh, 2020) are also relevant antecedents of employability. Furthermore, factors such as socioeconomic status, health, gender and sociodemographic characteristics also influence perceived employability (Bennet et al. , 2022; Hu et al.…”
Section: Perceived Employability In the Covid-19 Pandemic Contextmentioning
confidence: 99%